The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jtumed.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Designing a polytope for use in a broad-spectrum dengue virus vaccine

Abstract: Objectives Dengue virus surface proteins are often used in the development of vaccines that protect against dengue virus infection. However, the surface proteins on the four serotypes of dengue virus display high variation, which increases the difficulty of developing a vaccine that can protect against all viral strains. In this study, a polytope that is recognized by broadly neutralizing antibodies (bnAbs) was designed using conserved epitopes from the four serotypes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is reported that the conjugated polytope vaccine as a dendrimer constructed against HIV-1 elicited higher Th1 response [19]. In yet another instance, a polytope prediction from four conserved envelope protein of dengue virus serotypes was recognized by neutralizing IgGs [20]. Therefore, in this context, it is pertinent to build the molecular affinity based on spike protein sequences among the members of the family Coronaviridae and explore the possible multiepitope-based vaccine candidate for the population of Andhra Pradesh among Indian Asians.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the conjugated polytope vaccine as a dendrimer constructed against HIV-1 elicited higher Th1 response [19]. In yet another instance, a polytope prediction from four conserved envelope protein of dengue virus serotypes was recognized by neutralizing IgGs [20]. Therefore, in this context, it is pertinent to build the molecular affinity based on spike protein sequences among the members of the family Coronaviridae and explore the possible multiepitope-based vaccine candidate for the population of Andhra Pradesh among Indian Asians.…”
Section: Introductionmentioning
confidence: 99%